The Proliferation Capacity of Cultured Neural Stem Cells Promoted by CSF Collected from SAH Patients Correlates to Clinical Outcome - Yun-An Chen (Nature Portfolio, 2018)
Abstract Neurogenesis from endogenous neural stem cells (NSCs) might contribute to functional recovery after stroke based on animal studies; however, the relationship between neurogenesis and post-stroke outcome has rarely been demonstrated in humans. We prospectively collected cerebrospinal fluid (CSF) from 36 patients with subarachnoid hemorrhage (SAH). The CSF was added to the culture medium of the rat NSCs to test the effects on proliferation (proliferation index [PI], percentage of Ki-67 immunoreactive cells). We correlated the PI with functional outcome based on the modified Rankin Scale at 3 months post-SAH. Treatment with the CSF samples collected from SAH patients showed a higher PI compared with those collected from patients with normal pressure hydrocephalus and untreated controls (20.3 ± 8.8 vs. 8.2 ± 5.1 and 7.8 ± 3.0, P < 0.001), indicating proliferation-promoting factors in CSF after SAH. The PI was positively correlated with SAH volume (p = 0.025). For patients with lower SAH volume, patients with favorable outcome had a higher PI than those with poor outcome (20.8 ± 6.9 vs. 14.6 ± 4.3, p = 0.047). Using multivariable logistic regression analysis, the PI was a positive determinant for favorable outcome (odds ratio, 1.17; 95% confidence interval, 1.00 to 1.36) that more proliferation-promoting factors in CSF was associated with better functional outcome in SAH patients.